Gamma Knife treatment of recurrent CNS metastases of pancreatic origin: a case report and review of the literature. (2017) - Perni, Subha; Wang, Tony J; Lesser, Jerry; Mandigo, Christopher; Isaacson, Steven R; Horowitz, David P
Brain metastases (BM) of pancreatic origin are extremely rare. We review the literature around BM of pancreatic origin and describe a 38-year-old woman who developed BM 10 months after pancreaticoduodenectomy for treatment of pancreatic adenocarcinoma. She underwent resection and fractionated stereotactic radiotherapy followed by re-resection and Gamma Knife radiosurgery (GKRS) when the lesion recurred. She then developed two new BM, and was treated with GKRS. The patient is alive without progression 38 months after her most recent GKRS.